Generating Arbitrary Order Cylindrical Vector Beams With Inherent Transform Mechanism - Xiaoyu Weng; Luping Du; Aiping Yang; Changjun Min; Xiaocong Yuan (IEEE Photonics Journal, 2017)
Polarization converters that convert incident linearly polarized beams into arbitrary order cylindrical vector beams (CVBs) are derived with the Jones matrix theory. We reveal the existence of an inherent transform mechanism, which links the different order CVB converters. Based on this mechanism, CVB of any desired order can be achieved by the combination of the low-order CVB converters and half waveplates. The order of CVBs can be adjusted flexibly by changing the number of the first- and second-order vortex-waveplates, which are manufactured with the liquid crystal polarization modulation technique. This work facilitates the generation of arbitrary order CVBs, which may find valuable applications in optical trapping, optical communication, etc., as well.